Effects of C3+ ion irradiation on structural, electrical and magnetic properties of Ni nanotubes. (14th March 2018) - Shlimas, D I; Kozlovskiy, A L; Zdorovets, M V; Kadyrzhanov, K K; Uglov, V V; Kenzhina, I E; Shumskaya, E E; Kaniukov, E Y
Abstract: Ion irradiation is an attractive method for obtaining nanostructures that can be used under extreme conditions. Also, it is possible to control the technological process that allows obtaining nanomaterials with new properties at ion irradiation. In this paper, we study the effect of irradiation with 28 MeV C 3+ ions and fluences up to 5 × 10 11 cm −2 on the structure and properties of template-synthesized nickel nanotubes with a length of 12 μ m, with diameters of 400 nm, and a wall thickness of 100 nm. It is demonstrated that the main factor influencing the degradation of nanostructures under irradiation in PET template is the processes of mixing the material of nanostructures with the surrounding polymer. The influence of irradiation with various fluences on the crystal structure, electrical and magnetic properties of nickel nanotubes is studied.